Different Types of Review Approaches in Load Balancing Techniques in Cloud Computing Environment - Sindiya J, Arul; R, Pushpalakshmi (International Journal of Engineering and Technology, 2018)
Cloud computing is the most emerging and powerful technology in the IT world. The interesting features with enhancement facilities grab the attention of the researchers into its field. Its special kind is pay-as-you-go model for the consumers, by this way the user may this service as they want like as infrastructure, platform and software according to their needs. Cloud computing is an effective management system which built a great relationship between the consumer and the cloud ownerâ€™s. However there is a positive aspect still some negatives makes the cloud computing still research field. Some of the major drawbacks still to be discussed were fault tolerance, load balancing and security. The main concept need to be discussed is load balancing; it is mainly depend on requesting the resource services. Some of the key points in load balancing is optimization in resources usage, minimum response time, boost turnout and enabling free from needless burden. Another critical issue is increased user list and cloud application types. In this exploration we focused for Load balancing, how to balance and constructed a present day strategy in a distributed computing condition. Before construct an apparatus how about we do a point by point overview look into in different existing load balancing procedures and cloud analyst tool by various authors.Â Â